Educational technology on expressing breast milk: development and validation of a Serious Game - Vanessa Correa de Moraes; Lucimare Ferraz (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to develop and validate a Serious Game about expressing breast milk for occupational nurses working in agribusiness companies. Method: methodological study, carried out in three stages: construction, evaluation and validation of the Serious Game. This study was carried out in 2020, included nine nurses from an agribusiness company and nine specialists in obstetrics and health worker. Results: the game was structured in four phases: preparation for expressing milk (previous general care needed for expressing milk); methods for expressing milk (techniques to express milk); storage (care related to containers and temperature); the use of breast milk (transport, thawing method, and provision to the child). The content was validated by experts, obtaining an overall Índice de Validade de Conteúdo(Content Validity Index) of 86.72%. The game was tested by occupational nurses, and its "usability" was validated by the System Usability Scale instrument, with an index of 83.89%, and the "knowledge improvement" by the EGameFlow instrument with a mean of 6.52. Conclusion: the Expressing Milk Game technology obtained a high level of validity in terms of content and usability, demonstrating that it is an educational technology for health professionals to guide the maintenance of breastfeeding to nursing mothers.